Stretching representation : an analysis of the inclusion of ethnic groups in LatinAmerican representative institutions - Pinto, Hesaú Rômulo Braga (2024)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciência Política, Programa de Pós-Graduação em Ciência Política, 2024.